2007
DOI: 10.1002/ijc.23124
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of primary cytology and HPV DNA cervical screening

Abstract: Because cost-effectiveness of different cervical cytology screening strategies with and without human papillomavirus (HPV) DNA testing is unclear, we used a Markov model to estimate life expectancy and health care cost per woman during the remaining lifetime for 4 screening strategies: (i) cervical cytology screening at age 32, 35, 38, 41, 44, 47, 50, 55 and 60, (ii) same strategy with addition of testing for HPV DNA persistence at age 32, (iii) screening with combined cytology and testing for HPV DNA persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…Methods for calculating the ICER in six articles were; cost/ QALY (Mandelblatt et al, 2002b, Berkhof et al, 2010Chuck, 2010;Chow et al, 2010;Vijayaraghavan et al, 2009;2010a), in 13 studies the ICER were estimated by cost/LYG (Brown and Garber, 1999;Maxwell et al, 2002;Mandelblatt et al, 2002a;Goldie et al, 2001;2004;Kim et al, 2005;Bidus et al, 2006;Andres-Gamboa et al, 2008;Kulasingam et al, 2009;Levin et al, 2010;Sroczynski et al, 2011;Burger et al, 2012). Two studies did not report their ICER (Bistoletti et al, 2008;de Kok et al, 2012). The converted ICER of each country was compared with GDP per capita; in the USA, the ratio of ICER based on GDP per capita was approximately five fold (Goldie et al, 2004), and in other countries it was up to three times higher.…”
Section: Results By Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Methods for calculating the ICER in six articles were; cost/ QALY (Mandelblatt et al, 2002b, Berkhof et al, 2010Chuck, 2010;Chow et al, 2010;Vijayaraghavan et al, 2009;2010a), in 13 studies the ICER were estimated by cost/LYG (Brown and Garber, 1999;Maxwell et al, 2002;Mandelblatt et al, 2002a;Goldie et al, 2001;2004;Kim et al, 2005;Bidus et al, 2006;Andres-Gamboa et al, 2008;Kulasingam et al, 2009;Levin et al, 2010;Sroczynski et al, 2011;Burger et al, 2012). Two studies did not report their ICER (Bistoletti et al, 2008;de Kok et al, 2012). The converted ICER of each country was compared with GDP per capita; in the USA, the ratio of ICER based on GDP per capita was approximately five fold (Goldie et al, 2004), and in other countries it was up to three times higher.…”
Section: Results By Outcomesmentioning
confidence: 99%
“…In another project conducted in five less developed countries including; Kenya, Peru, South Africa and Thailand in 2005, Goldie suggested that applying HPV DNA testing just two times per lifetime i.e., at age 35 and 45 years was the most cost-effective, moreover, this strategy was dominated in India . In Sweden, Bisoleti et al showed that combined HPV DNA testing and cervical cytology three times per life time starting at age 32 was the most cost effective method (Bistoletti et al, 2008). Levin suggested rapid HPV DNA testing three times in a lifetime and starting at age 35 was the most cost-effective strategy at the national, township and county level in China (Levin et al, 2010).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
See 3 more Smart Citations